2020
DOI: 10.1101/2020.04.27.063875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

vmPFC drives hippocampal processing during autobiographical memory recall regardless of remoteness

Abstract: Our ability to recall past experiences, autobiographical memories (AMs), is crucial to cognition, endowing us with a sense of self and underwriting our capacity for autonomy.Traditional views assume that the hippocampus orchestrates event recall, whereas recent accounts propose that the ventromedial prefrontal cortex (vmPFC) instigates and coordinates hippocampal-dependent processes. Here we sought to characterise the dynamic interplay between hippocampus and vmPFC during AM recall to adjudicate between these … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 95 publications
4
18
1
Order By: Relevance
“…PLS does not assume a particular shape to the HRF, so the results are not biased by assuming a similar shape to the HRF across regions. Despite the sluggish HRF, our finding on the time course of prefrontal cortex preceding the hippocampus during reminder processing was motivated by, and is consistent with, these previous studies investigating how prefrontal-hippocampal networks dynamically interact to support retrieval (Barry et al, 2019;Fuentemilla et al, 2014;McCormick et al, 2020;St. Jacques, Conway, et al, 2011;St.…”
Section: Neuroimaging Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…PLS does not assume a particular shape to the HRF, so the results are not biased by assuming a similar shape to the HRF across regions. Despite the sluggish HRF, our finding on the time course of prefrontal cortex preceding the hippocampus during reminder processing was motivated by, and is consistent with, these previous studies investigating how prefrontal-hippocampal networks dynamically interact to support retrieval (Barry et al, 2019;Fuentemilla et al, 2014;McCormick et al, 2020;St. Jacques, Conway, et al, 2011;St.…”
Section: Neuroimaging Resultssupporting
confidence: 89%
“…St. Jacques, Conway, et al (2011) and St. Jacques, Kragel, & Rubin (2011) found that the medial prefrontal cortex is strongly engaged during both early memory construction and the subsequent elaboration phase, whereas the medial temporal lobe comes online more strongly during the elaboration phase. A comparable pattern of results was obtained by McCormick et al (2020) using MEG that affords greater temporal resolution than fMRI. In their study on retrieval of autobiographical memories acquired between 1 month to 5 years ago, vmPFC activation reached a peak at about 125 ms after initiation of retrieval, which preceded that of the hippocampus by 65 ms, for all but the most recent memories.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations